The analysis of the management strategies for the implementation of environmental legislation in the forest reserve of Ticoporo: Municipality Antonio José de Sucre, Barinas state, Venezuela (Ágora de Heterodoxias, 2015)
In Venezuela,  application of current  environmental legislation has not given the proper attention,  which creates a perception of a systematic violation of the right to live in a healthy, safe and ecologically balanced environment. The effective implementation of environmental laws promotes new forms of management with modern views within the public administration resulting in adequate protection of renewable natural resources. The research, developed through a documentary design, describes the current situation of Ticoporo Forest Reserve, located in the Sucre Municipality of Barinas State, as well as the management strategies for the implementation of current environmental regulations. The main results demonstrate the weakness of the Venezuelan State towards the investigation and prosecution of environmental crimes and explain how legal instruments have been unable to stop the disappearance of forest covers in this Area Under Regime of Special Administration (ABRAE for its acronym in Spanish).
Keywords: management strategies; SWOT analysis; environmental legislation; ABRAE; Ticoporo